Adhesive-bonded Repair for Cracked Metal Material of Remanufacture - Wenhua JIA; Chenbo YIN; Guo LI; Binghui JIA (Medžiagotyra, 2017)
By investigating Q235 steel containing center cracks commonly used in construction machinery, this study analyzed the stress intensity factors at the crack tip and the crack growth rate before and after the repair of the structure. The static mechanical properties and the stress-strain at different positions of the structure were studied before and after the repair. and The principle of adhesively-bonded patch repair was also verified. The obtained results showed that the static mechanical properties of the damaged metal structure were significantly improved to 80%. This was done through a single-sided repair using carbon/epoxy resin. A 90% improvement was accomplished through double-sided repair. DOI: http://dx.doi.org/10.5755/j01.ms.23.3.17168